#### Answer

x = -0.5

#### Work Step by Step

Simplifying
5x + -2.5(7 + -4x) = x + -7(4 + x)
5x + (7 * -2.5 + -4x * -2.5) = x + -7(4 + x)
5x + (-17.5 + 10x) = x + -7(4 + x)
Reorder the terms:
-17.5 + 5x + 10x = x + -7(4 + x)
Combine like terms: 5x + 10x = 15x
-17.5 + 15x = x + -7(4 + x)
-17.5 + 15x = x + (4 * -7 + x * -7)
-17.5 + 15x = x + (-28 + -7x)
Reorder the terms:
-17.5 + 15x = -28 + x + -7x
Combine like terms: x + -7x = -6x
-17.5 + 15x = -28 + -6x
Solving
-17.5 + 15x = -28 + -6x
Solving for variable 'x'.
Move all terms containing x to the left, all other terms to the right.
Add '6x' to each side of the equation.
-17.5 + 15x + 6x = -28 + -6x + 6x
Combine like terms: 15x + 6x = 21x
-17.5 + 21x = -28 + -6x + 6x
Combine like terms: -6x + 6x = 0
-17.5 + 21x = -28 + 0
-17.5 + 21x = -28
Add '17.5' to each side of the equation.
-17.5 + 17.5 + 21x = -28 + 17.5
Combine like terms: -17.5 + 17.5 = 0.0
0.0 + 21x = -28 + 17.5
21x = -28 + 17.5
Combine like terms: -28 + 17.5 = -10.5
21x = -10.5
Divide each side by '21'.
x = -0.5
Simplifying
x = -0.5